Load Balance Design of Google Cloud Compute Engine VPS with Round Robin Method in PT. Lintas Data Indonesia - Desmulyati, Desmulyati; Perdana Putra, Muhammad Rizki (Politeknik Ganesha Medan, 2019)
One of the providers of cloud computing services is the Google Cloud Platform developed by Google LLC. PT Lintas Data Indonesia as a vendor and distributor of technology devices is in dire need of a web server for the publicity of its products. At present, PT Lintas Data Indonesia's web server system still uses the services of hostgator hosting providers with packages with limited resources and also cannot implement system load balances and fail over on the current server system, in terms of latency access speed when pinging web servers in HostGator is quite high up to 200Ms. To improve the performance of a web server so that a load balance and fail over system can be implemented, migrating to the Google Cloud Platform environment is a solution that is expected to be able to handle existing problems. The advantages of Google Cloud Platform are servers that are rented for web servers in the form of Virtual Private Servers (VPS) so that they are easy to maintain and if you want to upgrade services. The addition of three web servers in the cluster with HAProxy server makes PT Lintas Data Indonesia's web server service more reliable in handling requests, load balances with round robin methods and fail over web servers and with HAProxy it is proven that it can increase up to 150% in handling latency issues previously it was around 30Ms.